Host-guest complexation behaviour of emissive calix[3]naphthobipyrrole toward aromatic guests. Issue 11 (2nd November 2018) - Sareen, Divya; Abebayehu, Abeje; Lee, Chang-Hee
ABSTRACT: A new hexapyrrolic macrocycle composed of three naphthobipyrrole units has been synthesized which exhibited different emission changes with hydrogen pyrophosphate and benzoate ions. Phosphate ions caused red shifting of the fluorescence band of calixnaphthobipyrrole while benzoate ions resulted in quenching of the same. The fluorescence quenching was further utilized for investigating binding preferences of the probe with neutral aromatic guest molecules substituted with groups having varied electron withdrawing abilities. The extent of quenching with the neutral guests increased with the increasing electron deficiency on the aromatic ring of the guest. The fluorescence quenching has been ascribed to electron transfer from the host to the guest species. GRAPHICAL ABSTRACT: